2023
DOI: 10.1109/tbme.2022.3222124
|View full text |Cite
|
Sign up to set email alerts
|

A Handheld Quantifiable Soft Tissue Manipulation Device for Tracking Real-Time Dispersive Force-Motion Patterns to Characterize Manual Therapy Treatment

Abstract: Low back pain (LBP) is one of the leading neuromusculoskeletal (NMSK) problems around the globe. Soft Tissue Manipulation (STM) is a force-based, noninvasive intervention used to clinically address NMSK pain conditions. Current STM practice standards are mostly subjective, suggesting an urgent need for quantitative metrics. This research aims at developing a handheld, portable smart medical device for tracking real-time dispersive force-motions to characterize manual therapy treatments as Quantifiable Soft Tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Both prior studies found instrument reliability between 60-90 • [16], and 70-90 • [17]. These manufactured devices used either uniaxial [16], or triaxial [17][18][19] compressive force sensors to determine force production, whereas the ELF measurement system utilizes a resistive-based technology that gauges the change in resistance at the sensing element. Triaxial sensors offer the advantage of providing three-dimensional force assessments which are valuable when assessing the complexities of different IASTM strokes (e.g., sweeping, fanning, j-shaped strokes) that may not be linear in their application.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both prior studies found instrument reliability between 60-90 • [16], and 70-90 • [17]. These manufactured devices used either uniaxial [16], or triaxial [17][18][19] compressive force sensors to determine force production, whereas the ELF measurement system utilizes a resistive-based technology that gauges the change in resistance at the sensing element. Triaxial sensors offer the advantage of providing three-dimensional force assessments which are valuable when assessing the complexities of different IASTM strokes (e.g., sweeping, fanning, j-shaped strokes) that may not be linear in their application.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, triaxial sensors, or simulated treatments on force plates may be necessary for future investigations to begin quantifying how different treatment strokes may be more effective at generating shear forces between the instrument and the soft tissue. Other devices have also been equipped with inertial measurement units and accelerometers to determine the three-dimensional orientation of the device in space as well as evaluate the angular motion of the treatment stroke [17][18][19]. Ultimately, these three-dimensional factors could be used to aid in the analysis and description of the various IASTM stroke types used in practice and whether specific strokes or force vectors are more effective for certain conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations